Phenotypic Characterization of Idiopathic Epilepsy in Border Collies - Santifort, Koen M.; Bertijn, Elise; Bhatti, Sofie F. M.; Leegwater, Peter; Fischer, Andrea; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2022)
The prevalence of idiopathic epilepsy (IE) within the Border Collie (BC) dog breed is high. The aim of the present retrospective study was to describe the phenotype of BCs with IE and assess correlations between phenotypic variables and owner-provided quality of life (QoL) scores. Data of BCs diagnosed with IE during the period of five consecutive years were retrospectively analyzed. All dogs were presented at least once to a veterinary neurology specialist at one of three veterinary referral hospitals and most were under continued medical care of that specialist. Owners were requested to complete a standardized online questionnaire including quality of life (QoL) scoring questions. Data of a total of 116 BC dogs were included for analysis. Median age at onset of first epileptic seizure (ES) was 33.5 months (6-188). A total of 34/86 (40%) of medically treated dogs received 1 antiseizure medication (ASM) and 52/86 (60%) received ≥2 ASMs. Phenobarbital was the most commonly employed ASM, used in 70/86 of treated dogs (81%). Four or more side effects were observed in 20/86 (23%) of treated dogs. Age at onset of first ES was significantly lower for dogs having experienced cluster seizures (CS), status epilepticus (SE) or both (median 27 months) versus dogs that had not experienced CS or SE (median 43 months). The QoL of BC with IE was scored with a median score of 7 out of 10. Owners scored their dog’s QoL to have declined by a median of 30% during the course of life with IE with 39% (37/95) of owners scoring their dog`s QoL to have declined by ≥50%. The present study confirms the association of age at onset of first ES with severity of epilepsy (e.g. presence of CS and/or SE) and further characterizes the phenotype of IE in BC dogs. QoL of BC can be heavily impacted by IE.